Madurez sexual en el mejillón chora Mytella guyanensis Lamarck, 1819 (Bivalvia: Mytilidae) del manglar en Jicaral, Puntarenas, Costa Rica - Sibaja, W. G. (Revista de Biología Tropical, 1986)
The mussel Mytella guyanensis is euryhaline and stenothermal according to the temperature and salinity of intersticies and the water mass. The sexes are separated and there is no sexual dimorphism; however, the gonadal tissue changes in consistency and color. When M. guyanensis reaches a length of 30-35 mm, it is middleaged, which takes about five months. During the annual reproductive cycle, M. guyanensis has many specimens in gametogenesis and with ripe gametes. The spawning maximum density peak is in April (end of the dry season). This reproductive behaviour in the chora shows that it is an iteroparous species. The average ratio for the sexes is 3.47 females for each male.